Co-workers' guanxi and construction workers' safety behavior: The mediating role of group identification - Chen, Huihua; Gong, Wenjing; Li, Hujun; Shi, Shiying (Frontiers in Public Health, 2022)
Background: The construction industry is charactered with high risk in China. And construction workers’ unsafe behavior is one of the significant reasons to cause safety accidents. The existing literature has identified some factors leading to construction workers' safety behavior, and these factors can be categorized from the prospective of the society, organization and individual. Co-works’ guanxi plays salient roles in the interactions of the construction workers, and thus, can exert effects on their decision-making upon safety behavior. However, there exit less studies investigating the mechanism how co-workers' guanxi influencing construction workers’ safety behavior. Objectives: The aim of this paper is to examine the relationship between co-workers' guanxi and construction workers' safety behavior, and the role of group identification in this relationship. Methods: Structural Equation Model (SEM). Results: Co-workers' guanxi can directly affect construction worker safety behavior, group identification functions as a mediating variable in the relationship between co-workers’ guanxi and construction safety behavior. Conclusions: The research results expand the measurement methods of co-workers’ guanxi and further enrich the research on the causation of workers’ safety behavior. Besides, this paper provides reference for construction managers to carry out guanxi-related safety management and help to formulate industrial regulations.